Comparing Subcutaneous Tissue Responses to Freshly Mixed and Set Root Canal Sealers - Derakhshan, Setareh; Adl, Alireza; Parirokh, Masoud; Mashadi Abbas, Fatemeh; Haghdoost, Ali Akbar (Iranian Endodontic Journal, 2010)
INTRODUCTION: The purpose of this study was to compare the subcutaneous tissue responses of freshly mixed or set endodontic root canal sealers (i.e. RoekoSeal, AH26, AH Plus) in Wistar Albino rats. MATERIALS AND METHODS: Seventy-two male albino rats weighing 200-250g were used. The animals were randomly divided into six groups of 12 rats each. Root canal sealers were implanted in subcutaneous tissue in both freshly mixed and set conditions. The animals were sacrificed after 7, 14, and, 60 days. After histological preparation and Hematoxylin and Eosin (H&E) staining, the specimens were evaluated for capsule thickness, severity and extent of inflammation, and necrosis. Results were statistically analyzed using Multivariate ANOVA test. RESULTS: Differences between set and freshly mixed root canal sealers were significant (P=0.014), but not significant between test materials and controls, except for capsule thickness and extent of inflammation between control and AH26 (P=0.019 and P=0.006 respectively). The interaction between the type of material and setting condition was significant for capsule thickness and severity of inflammation in AH26 specimens at 14 and 60 days (P=0.001). CONCLUSION: Based on the results of this study assessing the biocompatibility, both set and freshly mixed states can be used. [Iranian Endodontic Journal 2009;4(4):152-7]